2011
DOI: 10.1002/adma.201103087
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Oxide as a Gate Dielectric for Highly Transparent and Temperature‐Stable Zinc‐Oxide‐Based Thin‐Film Transistors

Abstract: Tungsten oxide is currently used as gate insulator in pH-sensing ion-sensitive field-effect transistors (ISFETs) and in electrochromic devices. Its great potential as a high-κ dielectric with high transparency and temperature stability is reported. Owing to the low gate voltage sweep necessary to turn the transistor on and off, a possible application could be as a low-voltage pixel driver in active-matrix displays in harsh environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…The obtained T 0 values are comparable with various other transition-metal oxides. [20][21][22][23][24][25] Equation ( 2) shows that the origin of the temperature shift between the two states is the density of states at the Fermi level, which can be estimated. In case of the partially switched state (Table 1 ), the density of states is one order of magnitude higher than that of the fully switched states.…”
Section: Communicationmentioning
confidence: 99%
“…The obtained T 0 values are comparable with various other transition-metal oxides. [20][21][22][23][24][25] Equation ( 2) shows that the origin of the temperature shift between the two states is the density of states at the Fermi level, which can be estimated. In case of the partially switched state (Table 1 ), the density of states is one order of magnitude higher than that of the fully switched states.…”
Section: Communicationmentioning
confidence: 99%
“…19 Consequently, a value for / ms ¼ À0: (1), with e i ¼ 80 being the relative dielectric permittivity of the gate insulator. 8 Fig. 3(b) and Table I contain the data of experimental values V exp on and the calculations of the turn-on voltages V th on .…”
mentioning
confidence: 99%
“…7 Accordingly, lower leakage currents and smaller gate sweep voltages DV SG in order to turn transistors on and off are feasible. Recently, 8 we demonstrated room-temperature deposited tungsten trioxide (WO 3 ) as a high-j gate dielectric in conjunction with n-ZnO channel material.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tungsten has recently been adapted as inverted-T refractory metal gate material where a relatively dense layer of chemical vapor deposition (CVD) tungsten is deposited on top of a thinner layer of less dense refractory metal, such as sputter deposition tungsten to promote adherence to a gate oxide layer grown on a silicon substrate. 9,10 Hence the characterization of tungsten oxide protective nano-films is important for both the subtractive and additive approaches in microelectronics manufacturing. Although it is known that the P-B ratio of tungsten is not protective in air (3.38 for WO 3 11 ) earlier CMP studies through electrochemical evaluations on tungsten demonstrated that it forms a protective oxide during the CMP applications.…”
mentioning
confidence: 99%